Concurrent Diagnoses of Cutaneous Sarcoidosis and Recurrent Metastatic Breast Cancer: More than a Coincidental Occurrence?. (5th September 2018) - Deen, Jacqueline; Mellick, Nick; Wheller, Laura
Abstract : Sarcoidosis is a rare, chronic, multisystem disease of unknown aetiology, characterised by non-caseating epithelioid cell granulomas. Its association with internal malignancy, in particular haematological cancers has been strongly documented in the literature, while its link with solid organ malignancies is less extensively reported. We present an atypical case of cutaneous sarcoidosis occurring in association with breast cancer recurrence in a 49-year-old female. Physician recognition of this link between sarcoidosis and internal malignancy is vital because many cases of sarcoidosis in association with neoplasia present initially, or even exclusively, with cutaneous sarcoidal lesions that may precede the development of cancer by several years, or as in our case, present as a cutaneous marker of concomitant underlying malignancy. Our case highlights the importance of age-appropriate cancer screening in additional to a routine work-up for systemic sarcoidosis in a patient with cutaneous sarcoidosis.